Understanding water reaction pathways to control the hydrolytic reactivity of a Zn metal-organic framework - Shoushun Chen; Zelin Zhang; Wei Chen; Bryan E. G. Lucier; Mansheng Chen; Wanli Zhang; Haihong Zhu; Ivan Hung; Anmin Zheng; Zhehong Gan; Dongsheng Lei; Yining Huang (Nature Communications)
Abstract Metal-organic frameworks (MOFs) are a class of porous materials that are of topical interest for their utility in water-related applications. Nevertheless, molecular-level insight into water-MOF interactions and MOF hydrolytic reactivity remains understudied. Herein, we report two hydrolytic pathways leading to either structural stability or framework decomposition of a MOF (ZnMOF-1). The two distinct ZnMOF-1 water reaction pathways are linked to the diffusion rate of incorporated guest dimethylformamide (DMF) molecules: slow diffusion of DMF triggers evolution of the initial MOF into a water-stable MOF product exhibiting enhanced water adsorption, while fast exchange of DMF with water leads to decomposition. The starting MOF, three intermediates from the water reaction pathways and the final stable MOF have been characterized. The documentation of two distinct pathways counters the stereotype that water exposure always leads to destruction or degradation of water-sensitive MOFs, and demonstrates that water-stable MOFs with improved adsorption properties can be prepared via controlled solvent-triggered structural rearrangement.